(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Jacob Mathew vs. State of Punjab & Anr. (2005) Case, Supreme Court said that the jurisprudential concept of negligence differs in civil and criminal law. What may be negligence in civil law may not necessarily be negligence in criminal law. For negligence to amount to an offence, the element of mens rea must be shown to exist. For an act to amount to criminal negligence, the degree of negligence should be much higher i.e. gross or of a very high degree. Negligence which is neither gross nor of a higher degree may provide a ground for action in civil law but cannot form the basis for prosecution. The husband of the first respondent (one Divakar) approached the appellant herein, complaining of a pain in the chest on 22.04.2002. On 25.04.2002, the appellant unsuccessfully attempted to perform an angioplasty on Divakar. Same day at around 3.30 p.m., by-pass surgery was conducted on Divakar in the same hospital. Subsequently, various complications developed and eventually Divakar died on 09.05.2002. On 14.05.2002, the first respondent lodged a complaint against the appellant and others under section 304A IPC. The Ld. Magistrate by his order dated 11.12.2006 came to the prima facie conclusion that there exists material to try the accused for the offence punishable under section 304A IPC. Andhra Pradesh High Court opined that the material on record “clearly shows negligence on the part of Appeallant” and declined to quash the proceedings. Later Supreme Court set aside the judgment under appeal and also the proceedings of the trial court dated 11.12.2006.